2018
DOI: 10.1038/s41598-018-20224-4
|View full text |Cite
|
Sign up to set email alerts
|

‘Photonic Hook’ based optomechanical nanoparticle manipulator

Abstract: Specialized electromagnetic fields can be used for nanoparticle manipulation along a specific path, allowing enhanced transport and control over the particle’s motion. In this paper, we investigate the optical forces produced by a curved photonic jet, otherwise known as the “photonic hook”, created using an asymmetric cuboid. In our case, this cuboid is formed by appending a triangular prism to one side of a cube. A gold nanoparticle immersed in the cuboid’s transmitted field moves in a curved trajectory. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…[28][29][30][31][32] Photonic nanojets are usually generated using symmetric structures, usually spherical, subjected to external illumination. 28,33 Previous work has explored a curved photonic nanojet, called the photonic hook, and its capacity for optical manipulation under continuous plane wave illumination 34 and pulsed plane waves. 35 It was shown that the maximum magnitude of the optical force generated by the photonic hook is near the wavelength of plasmon resonance excitation.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Photonic nanojets are usually generated using symmetric structures, usually spherical, subjected to external illumination. 28,33 Previous work has explored a curved photonic nanojet, called the photonic hook, and its capacity for optical manipulation under continuous plane wave illumination 34 and pulsed plane waves. 35 It was shown that the maximum magnitude of the optical force generated by the photonic hook is near the wavelength of plasmon resonance excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The PHP might be applied for manipulation of particles and liquids, particularly in on‐a‐chip in‐plane surface plasmon tweezers to enhance and to confine plasmonic fields created nearby the shadow surface of dielectric structures which can be engineered to yield curvilinear stable trapping sites involving enhanced optical forces. These possibilities also could be used for moving nanoparticles around obstacles …”
Section: Discussionmentioning
confidence: 99%
“…[5]. Last year, a second new class of curved light beam, the so-called "photonic hook" (PH), was formally put forward [6,7]. Unlike the Airy beam, the emerging PH is formed from a plane-wave-illuminated dielectric microparticle of which is composed of a cuboid and a triangular prism.…”
Section: Introductionmentioning
confidence: 99%
“…The shape features and field distributions of the PJs, under given conditions of certain environmental medium and illumination source, are depended on the geometrical morphologies and material properties of the investigated dielectric microparticles [17][18][19][20]. By introducing a triangular prism adjacent to the front side of a cuboid surface [6,7], the phase velocity and wave interference of the transmitted light in the upper and lower parts of the microparticle are different due to the break of particle's shape symmetry, and thus producing a curved PJ, i.e. PH.…”
Section: Introductionmentioning
confidence: 99%